Oxidation of melatonin and its catabolites, N-1-acetyl-N (2)-formyl-5-methoxykynuramine and N-1-acetyl-5-methoxykynuramine, by activated leukocytes - Silva, S. O.; Rodrigues, M. R.; Carvalho, SRQ; Catalani, L. H.; Campa, A.; Ximenes, Valdecir Farias [UNESP] (Blackwell Munksgaard, 2004)
N-1-acetyl-N-2-formyl-5-methoxykynuramine (AFMK) and N-1-acetyl-5-methoxykynuramine (AMK), two melatonin catabolites, have been described as potent antioxidants. We aimed to follow the kinetics of AFMK and AMK formation when melatonin is oxidized by phorbol myristate acetate (PMA) and lipopolysaccharide (LPS)-activated leukocytes. An HPLC-based method was used for AFMK and AMK determination in neutrophil and peripheral blood mononuclear cell cultures supernatants. Samples were separated isocratically on a C18 reverse-phase column using acetonitrile/H2O (25:75) as the mobile phase. AFMK was detected by fluorescence (excitation 340 nm and emission 460 nm) and AMK by UV-VIS absorbance (254 nm). Activation of neutrophils and mononuclear cells with PMA produces larger amounts of AFMK than activation with LPS, probably due to the lower levels of reactive oxygen species formation and myeloperoxidase (MPO) degranulation that occurs when cells are stimulated with LPS. The concentration of AMK found in the supernatant was about 5-10% (from 18-hr cultures) compared with AFMK. This result may reflect its reactivity. Indeed AMK, but not AFMK, is easily oxidized by activated neutrophils in a MPO and hydrogen peroxide-dependent reaction. In conclusion, we defined a simple procedure for the determination of AFMK and AMK in biological samples and demonstrated the capacity of leukocytes to oxidize melatonin and AMK.
Keywords: melatonin; mononuclear cells; myeloperoxidase; N-1-acetyl-5-methoxykynuramine (AMK); N-1-acetyl-N-2-formyl-5-methoxykynuramine (AFMK) neutrophils